Encryption Technology on Windows Workstation - Amdan, Zulkhaimi (Universiti Teknologi Petronas, 2004)
This paper discusses the development of a new method for encrypting text of information in Microsoft Windows environment. The purpose of this study is to develop a new type of encryption methodbased on RSAtechnique. In addition, the objective is to tighten the security of Windows platform by implementing a new way of encrypting users' information to prevent access by unauthorized users. This is achieved by trying to combine several techniques of securing and strengthening the RSA algorithm. One of the techniques that will be looked into is 'knocking', where the authorized users will have to perform a series of predetermined actions to validate their requests for the information in addition of the public key they have. This study is done because current encryption method in Windows environment is quite weak (e.g.: Windows password) and easily breakable using program like LC4(@stake LC4, about). Windows NT, 2000 and XP use Security Accounts Manager (SAM) file to store encrypted users passwords using RSA MD4 scheme(Windows NT SAM permission Vulnerability, bulletin), so if the RSA technique is enhanced it will enable a stronger and harder to break workstations. The result of this study will be an enhanced version of current encryption technology that is ready to be implemented or applied by interested parties.